The prevalence of posttraumatic stress among women requesting induced abortion. (December 2013) - Wallin Lundell, Inger; Sundström Poromaa, Inger; Frans, Örjan; Helström, Lotti; Högberg, Ulf; Moby, Lena; Nyberg, Sigrid; Sydsjö, Gunilla; Georgsson Öhman, Susanne; Östlund, Ingrid; Skoog Svanberg, Agneta
Abstract Objectives To describe the prevalence and pattern of traumatic experiences, to assess the prevalence of posttraumatic stress disorder (PTSD) and posttraumatic stress symptoms (PTSS), to identify risk factors for PTSD and PTSS, and to analyse the association of PTSD and PTSS with concomitant anxiety and depressive symptoms in women requesting induced abortion. Methods A Swedish multi-centre study of women requesting an induced abortion. The Screen Questionnaire – Posttraumatic Stress Disorder was used for research diagnoses of PTSD and PTSS. Anxiety and depressive symptoms were evaluated by the Hospital Anxiety and Depression Scale (HADS). Results Of the 1514 respondents, almost half reported traumatic experiences. Lifetime- and point prevalence of PTSD were 7% (95% confidence interval [CI]: 5.8–8.5) and 4% (95% CI: 3.1–5.2), respectively. The prevalence of PTSS was 23% (95% CI: 21.1–25.4). Women who reported symptoms of anxiety or depression when requesting abortion were more likely to have ongoing PTSD or PTSS. Also single-living women and smokers displayed higher rates of ongoing PTSD. Conclusions Although PTSD is rare among women who request an induced abortion, a relatively high proportion suffers from PTSS. Abortion seeking women with trauma experiences and existing or preexisting mental disorders need more consideration and alertness when counselled for termination.